Control of transient lower oesophageal sphincter relaxations and reflux by the GABAB agonist baclofen in patients with gastro-oesophageal reflux disease. Issue 1 (1st January 2002) - Zhang, Q; Lehmann, A; Rigda, R; Dent, J; Holloway, R H
Abstract : Background and aims: Transient lower oesophageal sphincter relaxations (TLOSRs) are the major cause of gastro-oesophageal reflux in normal subjects and in most patients with reflux disease. The gamma aminobutyric acid (GABA) receptor type B agonist, baclofen, is a potent inhibitor of TLOSRs in normal subjects. The aim of this study was to investigate the effect of baclofen on TLOSRs and postprandial gastro-oesophageal reflux in patients with reflux disease. Methods: In 20 patients with reflux disease, oesophageal motility and pH were measured, with patients in the sitting position, for three hours after a 3000 kJ mixed nutrient meal. On separate days at least one week apart, 40 mg oral baclofen or placebo was given 90 minutes before the meal. Results: Baclofen reduced the rate of TLOSRs by 40% from 15 (13.8–18.3) to 9 (5.8–13.3) per three hours (p<0.0002) and increased basal lower oesophageal sphincter pressure. Baclofen also significantly reduced the rate of reflux episodes by 43% from 7.0 (4.0–12.0) to 4.0 (1.5–9) per three hours (median (interquartile range); p<0.02). However, baclofen had no effect on oesophageal acid exposure (baclofen 4.9% (1.7–12.4) v placebo 5.0% (2.7–15.5)). Conclusions: In patients with reflux disease, the GABAB agonist baclofen significantly inhibits gastro-oesophageal reflux episodes by inhibition of TLOSRs. These findings suggest that GABAB agonists may be useful as therapeutic agents for the management of reflux disease.